The prevalence of symptoms and its correlation with sex in polish COVID-19 adult patients: Cross-sectional online open survey - Lewek, Pawel; Banaś, Izabela; Witkowski, Konrad; Lewek, Joanna; Kardas, Przemyslaw (Frontiers in Medicine, 2023)
BACKGROUND The understanding and treatment of COVID-19 has improved rapidly since December 2019 when SARS-CoV-2 was sequenced. However most papers on its symptomatology focus on hospitalized patients and address only a limited number of major presentations. Although differences depending on sex of COVID-19 patients have been previously confirmed (higher ICU admission and higher death rate for men), no publication has focused on sex-related differences in COVID-19 symptomatology. OBJECTIVE The aim of the study was to present a reliable list of COVID-19 symptoms and identify any differences in symptom prevalence depending on sex. RESULTS Survey responses were collected from 2408 participants (56.9% women) aged 18-90 (42± 12), 84.7% living in cities, who took part in the study between December 2020 and February 2021. Out of 54 predefined symptoms, the three most prevalent were fatigue (reported by 87.61% respondents), anosmia (73.74%) and headache (69.89%). Women were found to be more symptomatic than men, 31 symptoms occurred more often in women (including anosmia, headache and myalgias, P<.05). Subfebrility, fever and hemoptysis were more prevalent in men. Twelve symptoms (incl. hypothermia, sneezing and nausea) lasted longer in women than men (P<.05). Fatigue, cough, nasal dryness, xerostomia and polydipsia were the longest lasting symptoms of COVID-19 (lasted over 14 days). CONCLUSION Our study presents a wide range of symptoms, which may enable better recognition of COVID-19, especially in an outpatient setting. Understanding these differences in the symptomatology of community and hospitalized patients may help diagnose and treat patients faster and more accurately. Our findings also confirmed differences in symptomatology of COVID-19 between men and women, which may lay the foundation for a better understanding of the different courses of this disease in the sexes. Further studies are necessary to understand whether a different presentation correlates with a different outcome.